Peran Keluarga Dalam Mengontrol Gaya Hidup Pasien Hipertensi - Maswarni; Ningrum, Trisiwi Kusuma; Pratiwi Gasril (As-Shiha: Jurnal Kesehatan, 2024)
Hypertension or high blood pressure is an abnormal increase in blood pressure in the arteries continuously for more than a period. Hypertension is also defined as a systolic pressure of more than 140 mmHg and/or a diastolic pressure of more than 90 mmHg. Data from the 2010 Global Status Report on Noncommunicable Diseases from WHO states that 40% of developing economic countries have hypertension sufferers, while only 35% of developed countries have hypertension. Aim: To understand the role of the family in controlling the lifestyle of family members who suffer from hypertension. Research Method uses descriptive research methods. The population in the study were people in the Pandau Jaya Village area, Gading Marpoyan Housing, with a sample size of 21 respondents. The sampling method uses simple random sampling. The research instrument was a questionnaire about the role of the family in controlling the lifestyle of hypertensive patients using a Likert scale. The analysis used was univariate using SPSS version 17.0. Research Results: the majority of families have a good role as many as 16 respondents (76.2%, while the less good ones are 5 respondents (23.8%). Conclusions and Suggestions: It is hoped that families will increase their role so that they can be more optimal in accompanying family members who suffer hypertension